2013
DOI: 10.1161/circimaging.112.000133
|View full text |Cite
|
Sign up to set email alerts
|

Chronic Manifestation of Postreperfusion Intramyocardial Hemorrhage as Regional Iron Deposition

Abstract: Background— Intramyocardial hemorrhage frequently accompanies large reperfused myocardial infarctions. However, its influence on the makeup and the ensuing effect on the infarcted tissue during the chronic phase remain unexplored. Methods and Results— Patients (n=15; 3 women), recruited after successful percutaneous coronary intervention for first segment–elevation myocardial infarction, underwent cardiovascular magnetic resonance imaging… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
105
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 88 publications
(117 citation statements)
references
References 61 publications
(51 reference statements)
11
105
1
Order By: Relevance
“…20 It is well known that iron overload could cause cardiomyopathy with clinical manifestations, including decreasing the cardiac ejection fraction and arrhythmia. [37][38][39] Acidic environments prompt the transformation of iron from the oxidation state (Fe 3+ ) to the reduced state (Fe 2+ ), resulting in the generation of oxygen free radicals. Therefore, the toxic effect of myocardial iron is dynamic and is increased in the presence of metabolic acidosis.…”
Section: Discussionmentioning
confidence: 99%
“…20 It is well known that iron overload could cause cardiomyopathy with clinical manifestations, including decreasing the cardiac ejection fraction and arrhythmia. [37][38][39] Acidic environments prompt the transformation of iron from the oxidation state (Fe 3+ ) to the reduced state (Fe 2+ ), resulting in the generation of oxygen free radicals. Therefore, the toxic effect of myocardial iron is dynamic and is increased in the presence of metabolic acidosis.…”
Section: Discussionmentioning
confidence: 99%
“…Discussion Recent studies have shown that intramyocardial hemorrhage may be one of the strongest predictors of adverse outcome (15)(16)(17)(18)(19)(20). This has generated substantial interest in understanding the effects of reperfusion hemorrhage showed extensive myocardial damage accompanied by extensive inflammatory response.…”
Section: Cardiac Imaging: Acute Reperfusion Myocardial Hemorrhage Kalmentioning
confidence: 99%
“…Intramyocardial hemorrhage has been widely reported to be associated with larger infarctions and MVO after reperfusion both in animal models (8)(9)(10)(11) and in humans (12)(13)(14). It is important to note that intramyocardial hemorrhage has been shown to be a significant predictor of poor left ventricular (LV) remodeling (15)(16)(17)(18), late arrhythmogenic risk (19), and major adverse cardiovascular events (20).…”
Section: Patient Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…11,12 Interestingly, in a canine model of MI using T2* imaging CMR, these investigators have established that hemorrhage during the index MI is associated with late iron deposition and subsequent macrophage infiltration in the infarct zone, as well as important changes in surrogate markers of arrhythmic risk, including late potentials and QT dispersion. 13,14 However, validation of the association between infarct zone iron deposition with SCA risk in a population of patients with chronic MI has heretofore been lacking. The data presented by Cokic et al 15 LGE imaging (with a 5-SD cutoff) and peri-infarct zone assessment (with a 2/3-SD cutoff) were performed.…”
Section: See Article By Cokic Et Almentioning
confidence: 99%